2020
DOI: 10.1096/fj.202000610rr
|View full text |Cite
|
Sign up to set email alerts
|

Brain delivery of biologics using a cross‐species reactive transferrin receptor 1 VNAR shuttle

Abstract: Transferrin receptor 1 (TfR1) mediated transcytosis is an attractive strategy to enhance brain uptake of protein drugs, but translation remains a challenge. Here, a single domain shark antibody VNAR fragment (TXB2) with similar affinity to murine and human TfR1 was used to shuttle protein cargo into the brain. TXB2 was fused to a human IgG1 Fc domain (hFc) or to the amyloid‐β (Aβ) antibody bapineuzumab (Bapi). TXB2‐hFc displayed 20‐fold higher brain concentrations compared with a control VNAR‐hFc at 18 hours p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 31 publications
3
52
0
Order By: Relevance
“…On the other hand, deiodination and degradation would also be interpreted as removal of the antibody, and as discussed previously, elimination rate was similar for both antibodies. We have previously shown that iodine-125 radiolabelling is stable with very low levels of free iodine-125 in brain samples after antibody injection [ 8 ]. Still, it should be kept in mind that antibody and iodine-125 to some extent could be separate entities.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, deiodination and degradation would also be interpreted as removal of the antibody, and as discussed previously, elimination rate was similar for both antibodies. We have previously shown that iodine-125 radiolabelling is stable with very low levels of free iodine-125 in brain samples after antibody injection [ 8 ]. Still, it should be kept in mind that antibody and iodine-125 to some extent could be separate entities.…”
Section: Discussionmentioning
confidence: 99%
“…PET ligands such as 11 C-Pittsburgh compound B ( 11 C-PiB) and several later developed analogues bind to fibrillar Aβ, i.e. the form of Aβ found in insoluble amyloid plaques.…”
Section: Introductionmentioning
confidence: 99%
“…However, Aβ aggregation starts years before any clinical symptoms emerge, and it appears as the PET signal with amyloid radioligands such as 11 C-PiB become saturated rather early during disease progression (2,3). In contrast, nonfibrillar Aβ oligomers and protofibrils have been reported to display a more dynamic profile during the course of the clinical stages of the disease and may therefore be better biomarkers for disease severity than amyloid plaques (3,4).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations